PURSUING THE IDEAL OF INTEGRATION IN PENTECOSTAL THEOLOGICAL EDUCATION: - D. Quampah; M. Naidoo (Acta Theologica)
Theological colleges aim at training well-formed, well-resourced Christian leaders who possess a compelling personality and moral authority for impactful and transformational leadership. This is achievable largely through an integrated approach to the curriculum that places equal value on the development of the “head, heart, and hands”, the institutional ideal of holding the cognitive, affective and psychomotor dimensions of theological training in equilibrium. In addition, the contextual and contemporary relevance of such a curriculum is critical for maximum effect. The initial slow and hesitant approach of the Pentecostal movement to theological education has made them dependent on other Christian persuasions for models in theological education. This article reports on an empirical study to describe and evaluate the curriculum of Pentecost Theological Seminary in Ghana, in order to appreciate the extent of integration and relevance accomplished, and to contribute to institutional efforts at further integration.